Cytogenetics, genomics and biodiversity of the South American and African Arapaimidae fish family (Teleostei, Osteoglossiformes) - de Oliveira, Ezequiel Aguiar; Bertollo, Luiz Antonio Carlos; Rab, Petr; Ezaz, Tariq; Yano, Cassia Fernanda; Hatanaka, Terumi; Jegede, Oladele Ilesanmi; Tanomtong, Alongklod; Liehr, Thomas; Sember, Alexandr; Maruyama, Sandra Regina; Feldberg, Eliana; et al. (PloS one, 2019)
Osteoglossiformes represents one of the most ancestral teleost lineages, currently widespread over almost all continents, except for Antarctica. However, data involving advanced molecular cytogenetics or comparative genomics are yet largely limited for this fish group. Therefore, the present investigations focus on the osteoglossiform family Arapaimidae, studying a unique fish model group with advanced molecular cytogenetic genomic tools. The aim is to better explore and clarify certain events and factors that had impact on evolutionary history of this fish group. For that, both South American and African representatives of Arapaimidae, namely Arapaima gigas and Heterotis niloticus, were examined. Both species differed markedly by diploid chromosome numbers, with 2n = 56 found in A. gigas and 2n = 40 exhibited by H. niloticus. Conventional cytogenetics along with fluorescence in situ hybridization revealed some general trends shared by most osteoglossiform species analyzed thus far, such as the presence of only one chromosome pair bearing 18S and 5S rDNA sites and karyotypes dominated by acrocentric chromosomes, resembling thus the patterns of hypothetical ancestral teleost karyotype. Furthermore, the genomes of A. gigas and H. niloticus display remarkable divergence in terms of repetitive DNA content and distribution, as revealed by comparative genomic hybridization (CGH). On the other hand, genomic diversity of single copy sequences studied through principal component analyses (PCA) based on SNP alleles genotyped by the DArT seq procedure demonstrated a very low genetic distance between the South American and African Arapaimidae species; this pattern contrasts sharply with the scenario found in other osteoglossiform species. Underlying evolutionary mechanisms potentially explaining the obtained data have been suggested and discussed.
Keywords: Biodiversity; ryby; Jihoafrická republika; Fishes; ribozomální DNA; biodiverzita; genom; Genome; DNA, Ribosomal; Animals; Polymorphism, Single Nucleotide; jednonukleotidový polymorfismus; South Africa; zvířata